Altered synaptic plasticity and memory formation in nitric oxide synthase inhibitor-treated rats - Böhme, G A; Bon, C; Lemaire, M; Reibaud, M; Piot, O; Stutzmann, J M; Doble, A; Blanchard, J C (Proceedings of the National Academy of Sciences - PNAS, 1993)
Nitric oxide (NO) is a messenger molecule that is produced in the brain from the metabolism of L-arginine to L-citrulline. Growing evidence suggests a physiological role for NO in long-term potentiation (LTP). Since LTP is a form of synaptic plasticity thought to be involved in learning and memory, we have tested whether inhibition of endogenous NO production affects memory capacities of rats. We found that the NO synthase [L-arginine, NADPH:oxygen oxidoreductase (nitric oxide-forming), EC 1.14.13.39] inhibitor N omega-nitro-L-arginine, at doses blocking LTP in hippocampal slices, impairs spatial learning in a radial arm maze and olfactory memory in a social recognition test. In contrast, N omega-nitro-L-arginine left shock-avoidance learning unaffected. These results indicate that NO is involved in some but not all forms of memory and further support the existence of a causal link between LTP and spatial learning.